Security and performance of remote patient monitoring for chronic heart failure with Satelia® Cardio: First results from real-world use - Jourdain, Patrick; Picard, F; Girerd, N; Lemieux, H; Barritault, F; Seronde, MF; Labarre, JP; Pages, N; Bedel, C; Betito, L; et al. (Journal of Cardiology and Cardiovascular Medicine, 2023)
Background: Since 2019, remote patient monitoring (RPM) for patients with chronic heart failure (CHF) has been supported by the European Society of Cardiology. However, real-world data on the use of such solutions has been limited and not primarily based on patient-reported outcomes. The aim of this study was to describe the Satelia® Cardio solution in France within the French ETAPES funding program and assess the security and performance of its clinical algorithm. Methods: A retrospective observational study was conducted on CHF patients monitored by RPM through Satelia® Cardio. From September 1, 2018, to June 30, 2020, patients were included if they had completed over six months of follow-up. The risk of a possible CHF decompensation was categorized by the system in three levels: green, orange and red. The algorithm security and performance were assessed through the negative predictive value (NPV) of the prediction of hospitalization of a patient within seven days. Results: In total, 331 patients were included in this study with 36,682 patient self-administered questionnaires answered. Patients were mostly males (70.4%) and had a mean age of 68.1 years. The mean left ventricular ejection fraction (LVEF) was 35.4% (± 12.3) and 73.3% of patients had a LVEF ≤ 40%. The questionnaire response rate was 90.9%. A green status was generated for 95.3% of answers. There were 4.5% (n = 1,499) orange alerts and 0.2% (n = 74) red alerts. Overall, 92.1% of patients had at least one CHF related hospitalization and 31.7% (n = 105) of these cases were non-scheduled. The NPV at seven days was 99.43%. Conclusion: Satelia® Cardio is a feasible, relevant and reliable solution to safely monitor the cohorts of patients with CHF, reassuring cardiologists about patient stability.